Assessment of housing adequacy towards flood resilience in the municipality of Plaridel, Quezon Province, Philippines - Mazanhi, Patience (School of Urban and Regional Planning, University of the Philippines Diliman, 2025)
Flooding has plagued the world since time immemorial, and it has left much devastation in its wake. Among these, is the displacement of people from their homes. So far, adequate housing has played a vital role in mitigating the adverse effects of these disasters, for example, the location of peoples' homes in less vulnerable areas, and the quality of materials used have been known to reduce the impact of flooding on homes.